Comparison of the Thickness of the Anterior and Posterior Cortical Bone of the Fibula at the Site of Screw Fixation in Lateral Malleolar Fractures - Jaehyung Lee; Janghyun Kim; Sungkuk Chae; Seung ho Oh; Dongheon Cha (Foot & Ankle Orthopaedics)
Category: Ankle; Trauma Introduction/Purpose: In Weber type B rotational ankle fractures, fixation of the fibular fracture with interfragmentary lag screws and plates has traditionally been widely used. However, there have been instances in which interfragmentary lag screw fixation failed to offer sufficient stability particularly when the cortical bone thickness in the posterior part of the fibula was insufficient. In this study, our objective was to compare the thickness of the anterior and posterior cortical bone in the sagittal plane at the screw fixation site in surgically treated lateral malleolar fractures. Methods: A retrospective analysis of medical records was conducted on patients who underwent open reduction and internal fixation for Weber type B ankle fractures at our institution between March 2019 and December 2022. Exclusion criteria comprised patients without preoperative CT scans, those aged 19 years or younger, individuals with a history of prior surgery at the same site, and cases in which measuring cortical bone thickness was challenging due to severe fracture comminution. The radiographic assessment involved measuring and comparing the thickness of the anterior and posterior cortical bone at the fibular fracture site in the sagittal plane of the CT scans. Results: Among the total of 105 patients, 52 were male and 53 were female, with a mean age of 50.5 years. In the CT sagittal plane, the anterior cortical bone thickness of the fibula measured 2.40 mm, while the posterior thickness was 1.37 mm (p=0.005), indicating a statistically significant difference. Upon stratifying patients into male and female groups, it was observed that the anterior cortical bone thickness of the fibula was significantly greater in men compared to women (2.64 mm vs. 2.15 mm, p=0.002), and the posterior thickness was also significantly higher (1.51 mm vs. 1.25 mm, p=0.031). Conclusion: The assessment of fibula cortical bone thickness at the site of Weber B type lateral malleolar fractures revealed that the anterior cortical bone was thicker than the posterior cortical bone, and males exhibited greater thickness compared to females. We posit that these findings could provide valuable guidance in the selection of screw type and fixation direction during surgical interventions for lateral malleolar fractures.